Applications of Topological Methods in Molecular Chemistry - Chauvin, Remi.; Lepetit, Christine; Silvi, Bernard; Alikhani, Esmail; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This is the first edited volume that features two important frameworks, Hückel and quantum chemical topological analyses. The contributors, which include an array of academics of international distinction, describe recent applications of such topological methods to various fields and topics that provide the reader with the current state-of-the-art and give a flavour of the wide range of their potentialities.
Part I. Topological Methods : Definition, State of the Art and Prospects -- 1. On quantum chemical topology -- 2. Localization-Delocalization and Electron Density-Weighted Connectivity Matrices: A Bridge Between the Quantum Theory of Atoms in Molecules and Chemical Graph Theory -- 3. Extending the Topological Analysis and Seeking the Real-Space Subsystems: The Case of Non-Coulombic Systems with Homogenous Potential Energy Functions -- 4. Exploring Chemistry Through the Source Function for the Electron and Spin Densities -- 5. Emergent Scalar and Vector Fields in Quantum Chemical Topology -- 6. Topology of Quantum Mechanical Current Density Vector Fields Induced in a Molecule by Static Magnetic Perturbations -- 7. Topological Analysis of the Fukui Function -- 8. Topological Tools for the Study of Families of Reaction Mechanisms: the Fundamental Groups of Potential Surfaces in the Universal Molecule Context -- 9. Quantum Chemical Topology Approach for Dissecting Chemical Structure and Reactivity -- Part II. Topological Methods for the Characterization of π-Electron Delocalization and Aromaticity -- 10. Paradise Lost - π-Electron Conjugation in Homologs and Derivatives of Perylene -- 11. Rules of Aromaticity -- 12. Localized Structures at the Hückel Level, a Hückel-Derived Valence Bond Method -- 13. Magnetic Properties of Conjugated Hydrocarbons from Topological Hamiltonians -- Part III. Topological Methods for the Characterization of Weak Bonding Interactions -- 14. What Can be Learnt from a Location of Bond Paths and from Electron Density Distribution? -- 15. Following Halogen Bonds Formation with Bader's Atoms-in-Molecules Theory -- 16. Charge Transfer in Beryllium Bonds and Cooperativity of Beryllium and Halogen Bonds -- 17. A Complete NCI Perspective: From New Bonds to Reactivity -- 18. Diversity of the Nature of the Nitrogen-Oxygen Bond in Inorganic and Organic Nitrites in the Light of Topological Analysis of Electron Localisation Function (ELF) -- 19. Quantum Chemical Topology in the Field of Quasirelativistic Quantum Calculations. .
Keywords: Chemistry, Physical and theoretical; Topology; Theoretical Chemistry; Topology